Technical efficiency and its determinants of rice production in Cambodia - Sokvibol Kea; Hua Li; Linvolak Pich (Economies, 2016)
The present study aims to measure the technical efficiency and establish core factors affecting rice production in Cambodia. A four-year dataset generated from the central government document 'Profile on Economics and Social' of 25 entire provinces between 2012 and 2015 and the stochastic production frontier model (SFA) was applied. The results indicated that the level of output (quantity) of Cambodian rice production varied according to the different level of capital investment in agricultural machineries, total rice actual harvested area, and technical fertilizer application within provinces. Furthermore, evidence revealed that the overall mean efficiency of rice production is 78.4%, which implies that there is still room to further improve technical efficiency given the same level of inputs and technology. More importantly, the findings revealed that irrigation, production techniques and amount of agricultural supporting staff are the most important influencing factors of rice production's technical efficiency in Cambodia. In conclusion, the present study strongly recommends the development of irrigation systems and good water management practices to be considered and bring about more effective actions by the central government as well as related agencies for improving rice production in Cambodia in addition to capital investment and improving technical skills of supporting staff and rural farmers.
Keywords: C01; C33; C51; C87; E23; M11; O33; 330; technical efficiency; SFA; rice production; Cambodia; agriculture; productivity